ANALISIS MAKNA PUISI “TUHAN BEGITU DEKAT” KARYA ABDUL HADI W.M DENGAN MENGGUNAKAN PENDEKATAN SEMIOTIK - Yuli Yulianti Nurjannah; Putri Ayu Chandra Agustina; Cucu Aisah; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Analyzing a literary work can be done through various ways or approaches. One approach that can be used in analyzing poetry is the semiotic approach. The semiotic approach is an effort to reveal meaning based on the signs that exist in the poem. The dominant sign in the Lord's poem So Close is the index. An index is a sign that gives an idea of the causal relationship between the object. The object used in this poem has a difference in each stanza. Although the object used is different, but has the same meaning, which explains how the relationship of god with his servant. The method used is qualitative description using interpretation technique and read refer.